2008
DOI: 10.1007/s10567-008-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Meta-Analysis of Triple P-Positive Parenting Program Using Hierarchical Linear Modeling: Effectiveness and Moderating Variables

Abstract: A meta-analysis encompassing all studies evaluating the impact of the Triple P-Positive Parenting Program on parent and child outcome measures was conducted in an effort to identify variables that moderate the program's effectiveness. Hierarchical linear models (HLM) with three levels of data were employed to analyze effect sizes. The results (N=55 studies) indicate that Triple P causes positive changes in parenting skills, child problem behavior and parental well-being in the small to moderate range, varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
344
3
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(371 citation statements)
references
References 131 publications
16
344
3
8
Order By: Relevance
“…These findings diverge from those reported in previous studies conducted by the program developer or local license holders on Triple P as a universal prevention strategy (McTaggart and Sanders 2003;Heinrichs et al 2006) and the overall assessment in the meta-analysis by Nowak and Heinrichs (2008). However, they are similar to two other independent trials: In particular, de Graaf et al (2009) found no effects of Primary Care Triple P on any dimension of child problem behavior in a trial in the Netherlands, although a positive effect was found on lax parenting.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…These findings diverge from those reported in previous studies conducted by the program developer or local license holders on Triple P as a universal prevention strategy (McTaggart and Sanders 2003;Heinrichs et al 2006) and the overall assessment in the meta-analysis by Nowak and Heinrichs (2008). However, they are similar to two other independent trials: In particular, de Graaf et al (2009) found no effects of Primary Care Triple P on any dimension of child problem behavior in a trial in the Netherlands, although a positive effect was found on lax parenting.…”
Section: Discussioncontrasting
confidence: 96%
“…It is amongst the most thoroughly evaluated parent training programs in the world. A metaanalysis by Nowak and Heinrichs (2008) identified 55 studies that had assessed the effectiveness of Triple P on a variety of outcome measures. The study reports significant positive effects on parenting (Cohen's d00.38), child problem behavior (d00.35), and parental well-being (d00.17).…”
Section: The Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTA study does support the use of psycho-social approaches with ADHD children as a way of reducing oppositional and noncompliant behavior [7]. The value of such approaches for the treatment of oppositional behavior is confirmed by trials of parent training interventions developed for noncompliant children based on generic behavior modification principles such as Incredible Years [39] and Triple P [21]. These have also been shown to be effective in reducing oppositional behavior in ADHD children [2,17].…”
Section: Introductionmentioning
confidence: 99%
“…Triple P focuses on: (a) basics of communication skills, reinforcement, monitoring, etiology of conduct disorders, goals of parenting and systematic behavior observation, (b) learning principles and promotion of healthy development, (c) strategies to deal with child problem behavior, parenting routines, and (d) plans of common activities and coping with situations at risk. Efficacy and effectiveness of Triple P have been internationally demonstrated (e.g., de Graaf, Speetjens, Smit, de Wolff, & Tavecchio, 2008;Markie-Dadds & Sanders, 2006;Nowak & Heinrichs, 2008;Sanders, Bor, & Morawska, 2007).…”
mentioning
confidence: 99%